Penggunaan Media Gambar Dan Kartu Huruf Dalam Meningkatkan Kemampuan Bahasa Awal Anak Usia Dini - Sriviani Nguru; Beatriks Tanau; Merlin Missa; Desi Sopa; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Picture media is a visual media in the form of illustrations, photos, or symbols used to help children recognize objects, vocabulary, and meanings concretely. Letter cards are learning media in the form of cards containing letters of the alphabet, usually accompanied by pictures or words, to stimulate the ability to recognize letters and sounds of language. The purpose of this study was to determine the effect of the use of picture media and letter cards on the early language skills of early childhood (AUD) 3-6 years. The method in this study is quantitative. The sampling technique was purposive sampling, namely children aged 3-6 years. The respondents of this study were 20 children aged 3-6 years at Obenasi Kindergarten, Takari District. The data collection technique used a questionnaire with an instrument in the form of a picture media scale and letter cards. The data analysis technique was simple linear regression. The results of the data analysis and discussion that have been carried out, it can be concluded that the use of picture media and letter cards on the early language development of early childhood (AUD) at Obenasi Kindergarten, Takari District has a positive and significant effect on the early language skills of early childhood. This is evidenced by the results of the simultaneous test (F test), which showed a calculated F value of 10.134 with a significance level of 0.005 (<0.05), thus declaring the regression model significant and suitable for use. The coefficient of determination analysis results showed an R-square value of 0.360, meaning that 36% of the variation in early childhood language skills can be explained by the use of pictures and letter cards, while the remaining 64% is influenced by factors outside this research model. It is hoped that the use of pictures and letter cards in Obenasi Kindergarten will provide effective and relevant learning to improve early childhood language skills.